2020
DOI: 10.1111/cobi.13502
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive plan for prioritizing road sections for fencing to reduce animal mortality

Abstract: Mortality of animals on roads is a critical threat to many wildlife populations and is poised to increase strongly because of ongoing and planned road construction. If these new roads cannot be avoided, effective mitigation measures will be necessary to stop biodiversity decline. Fencing along roads effectively reduces roadkill and is often used in combination with wildlife passages. Because fencing the entire road is not always possible due to financial constraints, high-frequency roadkill areas are often ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Then, the share of land covered by each land cover class was quantified in the buffer area surrounding road segments, in order to obtain a gradient for each land cover class and road segment length. Buffer extents were chosen to account for uncertainty around crossing sites (Červinka et al 2015;Valerio et al 2019), and the trade-off between identifying hotspots and covering a large area, which is shown to be most effective at a scale between 200 and 2000 m (Spanowicz et al 2020).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Then, the share of land covered by each land cover class was quantified in the buffer area surrounding road segments, in order to obtain a gradient for each land cover class and road segment length. Buffer extents were chosen to account for uncertainty around crossing sites (Červinka et al 2015;Valerio et al 2019), and the trade-off between identifying hotspots and covering a large area, which is shown to be most effective at a scale between 200 and 2000 m (Spanowicz et al 2020).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…However, by contrast, wolf mortality was highest on motorways elsewhere in Spain, with fencing being reported as a key predictor in roadkill (Colino-Rabanal et al 2011). Whilst traffic volume is an obvious explanation of mortality, the effects of fencing may not be immediately apparent, as they are usually thought of as an effective mitigation tool in reducing roadkill (Spanowicz et al 2020). However, if a wolf enters a motorway through gaps in fencing, they may be forced to spend more time on the road searching for an exit, thus heightening their chances of being killed.…”
Section: Discussionmentioning
confidence: 98%
“…An increasing focus should be allocated to identify drivers of wolf mortality on primary roads (class II) in our study area (Fig. 4), in order to identify segments of roads where mitigation efforts should be prioritised (e.g., crossing structures such as bridges, underpasses, or fencing; Grilo et al 2010;Van der Ree et al 2015;Spanowicz et al 2020). Research has indicated that wildlife-vehicle collisions are not random events, but clustered (Clevenger et al 2003;Ramp et al 2006;Morelle et al 2013;Keken et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Short wildlife fences may not sufficiently reduce the risk of accidents [63][64][65][66]; however, they are economically more affordable. Long fences are less economically efficient, but may perform better [18,63,66] on roads with the highest traffic intensity [67].…”
Section: Evaluation Of Wildlife Fencesmentioning
confidence: 99%